Role of Agroforestry in Fodder Production in Himachal Pradesh - Gupta, Manoj; Kumar, Purushottam; Rana, Rachita (Indian Journal of Agroforestry, 2020)
Livestock is an important and inseparable component of the hill farming systems. Farmer is heavily dependent upon agroforestry component of farming system for regular supply of the fodder to livestock. Green fodder is a crucial input in scientific dairy management and its scarcity in Himachal Pradesh during summer and winter months is biggest bottleneck in maintaining livestock productivity. Cultivation of fodder is almost negligible due to small, marginal and rainfed land holdings and tree fodder is the only green fodder available in most parts of state during winter season. Hence this study was conducted to highlight the socio-economic importance of the agroforestry in relation to livestock sector in Himachal Pradesh. This study was carried out in the Sirmour district of Himachal Pradesh and data was collected from 90 farmers through interview method on specifically prepared schedules. Majority of the farmers were small and marginal, yet, they had sizable area under silvo-pastoral and agri-silvi system. On an average, 6-7 adult cattle units were being reared by the farmers and cattle was the preferred livestock species. Maize and wheat were the major agricultural crops on rainfed fields, while cash crops like vegetable were preferred on irrigated plots. Average daily fodder requirement of the farmers was about 1.6 q. Own lands contribute most towards fodder needs of the farmer followed by forests and common lands. Nearly 75 trees were being grown by an average farmer, out of which nearly 33 were on bunds while 37 were on pasture lands. Nearly half of these trees were primarily for fodder needs, rest were for fuelwood etc. Non-availability of good quality green fodder is the major hurdle in development of scientific dairy sector in Himachal Pradesh. Development and demonstration of agroforestry models can go a long way in progress of dairy sector in Himachal Pradesh.